Upaya Pemerintah Daerah Menertibkan Usaha Tambak Udang yang Belum Berwawasan Lingkungan (Studi kasus Kecamatan Batang Anai Kabupaten Padang Pariaman) - Yati, Lisa Medika; Rembrandt, Rembrandt; Syofiarti, Syofiarti (Universitas Ekasakti, 2023)
This research is motivated by the development of shrimp farming businesses, which are always growing in Batang Anai District, Padang Pariaman Regency. However, most of the shrimp ponds were built without complying with environmental legal instruments. The research method used is qualitative descriptive analysis with an empirical juridical approach in addition to a normative approach, as well as data collection techniques such as interviews, observation, literature study, and documentation. Analyzed using four components of analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the research obtained by the author are: Firstly, most of the shrimp farming businesses in Batang Anai sub-district are not environmentally friendly due to the difficulties of entrepreneurs in processing Amdal documents. Second, the government has made efforts to regulate shrimp farming businesses that are not yet environmentally friendly in Batang Anai District, but the efforts made by the government have not been effective. It would be better for the Regional Government of Padang Pariaman Regency to form a regional Amdal to make it easier for entrepreneurs to process business permits.